2002
DOI: 10.1159/000065280
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of an In-Center Daily Hemodialysis Program

Abstract: Short duration daily hemodialysis (DHD) emerges as a well-tolerated alternative to standard hemodialysis (SHD). In this prospective study 5 patients in SHD were recruited to participate in an in-center DHD program. The SHD consisted of 3 sessions of 4 h each per week. Nonproportional mixture machines without an ultrafiltration control device and low flow dialyzers were used. For DHD, dialysis equipment and procedures were kept the same. Dialysis sessions, however, began at 6 p.m. (from Monday to Saturday) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 12 publications
3
35
0
1
Order By: Relevance
“…This pattern may reflect growing fatigue with the daily dialysis regimen, as reported in a prospective study of five daily in-center hemodialysis patients. 32 However, estimates of relative survival in later intervals mostly rely on follow-up data from patients who initiated DHHD in 2005 and 2006. We found that survival was better for patients who initiated DHHD in 2007 than for their predecessors, suggesting serial improvement in patient training and technique execution.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern may reflect growing fatigue with the daily dialysis regimen, as reported in a prospective study of five daily in-center hemodialysis patients. 32 However, estimates of relative survival in later intervals mostly rely on follow-up data from patients who initiated DHHD in 2005 and 2006. We found that survival was better for patients who initiated DHHD in 2007 than for their predecessors, suggesting serial improvement in patient training and technique execution.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in systolic or mean arterial BP were reported in 10 of 11 studies (10,14,16,17,(22)(23)(24)27,29,31), whereas six of eight studies found no statistically significant change in phosphate or phosphate binder dose with DHD at 3 to 24 mo of follow-up (12,14,16,24,26,27). Health-related quality of life improved in some studies but not in others.…”
Section: Outcomes With Dhdmentioning
confidence: 97%
“…Health-related quality of life improved in some studies but not in others. Improvements were seen in hematocrit, hemoglobin, or erythropoietin dose in 7 of 11 studies (14,16,17,22,24,29,31). Albumin increased in 5 of 10 studies (11,16,18,22,29).…”
Section: Outcomes With Dhdmentioning
confidence: 97%
“…Such objectives are more easily achieved in longer and/or more frequent dialysis regimens. [6][7][8][9][10] There is evidence that the longer treatment, even in CHD, is associated with a smaller risk of death, regardless of the Kt/V achieved. Japan, where patients frequently undergo dialysis for four to five hours per session, has the lowest HD mortality rate in the world.…”
Section: Limitations O F T H E C O N V E N T I O N a L R E G I M E Nmentioning
confidence: 99%
“…Patients on DHD show a significant improvement in several clinical, laboratory, and echocardiographic parameters. 9,10,20,22 Patients also improve their quality of life. 23 As previously mentioned, patients on CHD have only approximately 25% of remaining life expectancy when beginning dialysis as compared with the general population.…”
Section: Short D a I Ly H E M O D I A Ly S I Smentioning
confidence: 99%